2005
DOI: 10.1039/b417272h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and complexation properties of DTPA-N,N″-bis[bis(n-butyl)]-N′-methyl-tris(amide). Kinetic stability and water exchange of its Gd3+complex

Abstract: A novel DTPA-tris(amide) derivative ligand, DTPA-N,N''-bis[bis(n-butyl)]-N'-methyl-tris(amide)(H2L3) was synthesized. With Gd3+, it forms a positively charged [Gd(L3)]+ complex, whereas with Cu2+ and Zn2+ [ML3], [MHL3]+ and [M2L3]2+ species are formed. The protonation constants of H2L3 and the stability constants of the complexes were determined by pH potentiometry. The stability constants are lower than those for DTPA-N,N''-bis[bis(n-butyl)amide)](H3L2), due to the lower negative charge and reduced basicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…In the case of [Gd(L 2 )] 2-, the lower basicity of the donor groups results in lower ability of binuclear complex formation (see also the values of stability constants of dinuclear species, For the H 5 dtpa and its various amide derivatives, all the gadolinium() complexes have similar kinetic stability comparing to each other. [26][27][28]] Surprisingly, we found that the gadolinium() complexes with H 5 dtpa-analogues derived on the central nitrogen atom by the phosphorus acid pendant arm are much less kinetically stable with the halflife times about two to three orders of magnitude shorter. This can probably be attributed to a steric strain in the new complexes, which coordination sphere is not so compact and which can be attacked by a proton or by an additional metal ion.…”
Section: Dissociation Kineticsmentioning
confidence: 81%
See 1 more Smart Citation
“…In the case of [Gd(L 2 )] 2-, the lower basicity of the donor groups results in lower ability of binuclear complex formation (see also the values of stability constants of dinuclear species, For the H 5 dtpa and its various amide derivatives, all the gadolinium() complexes have similar kinetic stability comparing to each other. [26][27][28]] Surprisingly, we found that the gadolinium() complexes with H 5 dtpa-analogues derived on the central nitrogen atom by the phosphorus acid pendant arm are much less kinetically stable with the halflife times about two to three orders of magnitude shorter. This can probably be attributed to a steric strain in the new complexes, which coordination sphere is not so compact and which can be attacked by a proton or by an additional metal ion.…”
Section: Dissociation Kineticsmentioning
confidence: 81%
“…[27,28] Therefore, the kinetic data had to be acquired by a stopped-flow technique. Dissociation reactions were performed in high excess (10-70×) of the concurrent metal ion (Cu 2+ or Eu 3+ ), ensuring pseudofirst-order reaction conditions, and in buffered solutions (pH in range 3.5-5.7).…”
Section: Dissociation Kineticsmentioning
confidence: 99%
“…Since the basicity of the amide oxygen increases in the following order, -CO-NH 2 < −CO-NHR < −CO-NR 2 , the decrease in the log K M(L) values is smallest for complexes of DTPA-bis-amides derived from secondary amines (e.g., DTPA-B(BBuA)). It has been argued that this drop in stability does not preclude the use of these complexes in vivo because the stability constants of DTPA-bisamide ligands with endogenous Ca 2+ , Zn 2+ , and Cu 2+ decrease even more dramatically under in vitro conditions [1,30]. However, this argument assumes that the toxicity of these complexes is largely due to transmetallation (competitive removal of the Gd 3+ by one of these endogenous ions) and this may not be the case.…”
Section: Stability Of Metal-ligand Complexesmentioning
confidence: 87%
“…Formation of dinuclear complexes is even more pronounced for ligands having higher denticity (e.g., EGTA, BAPTA, or TTHA), or for ligands that contain phosphinate or alcoholic OH groups positioned between two iminodiacetate units (BIMP or HPDTA) [63,64]. The formation of dinuclear complexes was first assumed not to occur for DTPA-bisamide derivatives [1] yet dinuclear Cu 2 (L) and Zn 2 (L) species have been reported for DTPA-bisbutylamide and DTPA-bisdibutylamide [30].…”
Section: Stability Of Metal-ligand Complexesmentioning
confidence: 99%
See 1 more Smart Citation